Carbon dioxide emissions evaluations and mitigations in the building and traffic sectors in Taichung metropolitan area, Taiwan. (1st September 2019) - Chang, Chou-Tsang; Yang, Chih-Hsuan; Lin, Tzu-Ping
Abstract: Since the beginning of the industrial revolution, the atmospheric CO2 level has been continuously increasing because of the overall energy use in urban areas that generates excessively high levels of CO2 emissions. This study reviewed the relevant literature, then adopted the Taichung metropolitan area as the research target and assessed carbon emissions with respect to buildings, traffic, and carbon sinks. The overall carbon budget of the metropolitan area was mapped following a statistical analysis of the numerical data and urban space information. The results of this study indicated that the annual average urban carbon emissions consist of 67.6% building carbon emissions, 30.5% traffic carbon emissions, and −1.9% carbon sink absorption. In this study, a multiple regression model was used to calculate the floor area of each building. This study also determined that densely populated areas emitted higher levels of carbon than less populated areas. For every square meter of total floor area, 16.51 tCO2 /m 2 ·yr of carbon were emitted from buildings every year. Recommended policies for the city government to implement in the future were organized and used to establish three simulation scenarios of the various implementation stages. The results indicated that adjusting the floor area ratio of buildings is the optimal carbon reduction approach, achieving a reduction of at most 620, 363 tons of carbon per year, and multi-scale carbon reduction hotspots were mapped out. In addition, the high-resolution grid was used to present the multi-scale carbon budget results, which helps government agencies to formulate follow-up priority carbon reduction strategies and urban carbon neutral policies. Graphical abstract: Image 1 Highlights: Urban carbon footprint is influenced by buildings, traffic, and carbon sinks. The overall urban carbon emissions consist of 67.6% building carbon emissions. Energy hotspots are located in specific urban blocks and at the intersections of main roads. Building were emitted 16.51 tCO2 /m 2 ·yr for every square meter of floor area. The overall carbon budget of the Taichung Metropolitan Area was mapped.